Polarimetric wide-angle common midpoint pRES survey near central front of Ekström Ice Shelf, East Antarctica - Falk M Oraschewski; M Reza Ershadi; Reinhard Drews (PANGAEA, 2025)
Glacial ice can be dielectrically anisotropic due to ice fabric anisotropy, which describes a preferred orientation of ice crystal lattices, as well as structural anisotropy in the upper firn layer. Direct observation of the vertical dielectric anisotropy with radar polarimetry requires wide-angle radar configurations that achieve oblique ray paths. This dataset comprises results of a polarimetric common midpoint (CMP) survey acquired with the (Autonomous) phase-sensitive Radio Echo Sounder (pRES) near the central front of Ekström ice shelf, Droning Maud Land, East Antarctica. The data were acquired on February 24, 2023, with logistic support from Neumayer III station (Alfred-Wegener-Institut Helmholtz-Zentrum für Polar- und Meeresforschung, 2016). Transmitter and receiver were connected with 4 x 25 m coaxial cables, each. Antenna distances were increased from 10 m to 200 m in 2 m steps, with the CMP line being oriented toward magnetic north. At each posting three measurements (HH, VV, HV) were obtained, indicating parallel (H) and perpedicular (V) polarization of transmitter and receiver relative to the CMP line.